Unlocking the Potential of Niosomes: A Comprehensive Review - Ritthe, Punam V.; Fugate, Dr. Ajay; Shafi, Dr. Sameer; Rudrurkar, Muktai N.; Kazi, Anis J.; Patil, Sneha R.; Sante, Rohini U.; Shaikh., Imran (Asian Journal of Pharmaceutical Research and Development, 2024)
Niosomes are vesicular systems that are similar to liposomes and are obtained by hydrating synthetic nonionic surfactants, with or without incorporating cholesterol or their lipids. They can be used as carriers for amphiphilic and lipophilic drugs and are biodegradable, biocompatible, non-immunogenic, and flexible in their structural characterization. Niosomes have been widely evaluated for controlled release and targeted delivery for the treatment of cancer, viral infections, and other microbial diseases. They can entrap both hydrophilic and lipophilic drugs and prolong the circulation of the entrapped drug in the body. By encapsulating drugs in a vesicular system, the existence of the drug in the systemic circulation can be extended, and penetration into target tissue can be enhanced, reducing toxicity if selective uptake can be achieved. This review article focuses on the advantages, disadvantages, types, preparation methods, factors affecting, characterizations and applications of niosomes.